Injury Risk, Concussions, Race, and Pay in the NFL - Quinn Keefer; Thomas J. Kniesner (Institute of Labor Economics (IZA), 2023)
We make two main contributions to the literature on work-related injury risk and economic outcomes in the context of American professional football. One is to examine an increasingly important specific injury, concussions, and compare its subsequent economic effects to those of other types of football injuries. Our other contribution is to study the role of race in understanding injury risk and severity and their resulting economic consequences, which has been overlooked in previous sports injury research. Using a specific position, tight ends, which allows conditioning on fine-grained relevant measures of player demographics, playing time, and performance, we find that whether a player continues to play NFL football from year to year is affected by type of injury and the player's race. We calculate that the average ex post loss in annual compensation from a concussion is about 7%. Moreover, the effect of games missed due to concussion on continued employment is triple that of other injuries. Being white positively affects length of playing career independent of the measured productivity of the players involved. The racial gap in career length is approximately equal to the effect of an additional game missed from concussion. With respect to heterogeneity in the effects of injuries, both concussions and other injury types affect ex post economic outcomes equally for white and nonwhite players. Both injuries and race affect compensation solely through their effects on career length.
Keywords: D81; J31; J81; Z21; Z22; C23; 330; work-related injuries; concussions; race; pay; NFL; tight ends; panel data